2019
DOI: 10.3390/en12020324
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Expansion Pathways for a Wind and Solar Based Power Supply and the Impact of Advanced Technology—A Case Study for Germany

Abstract: Wind and solar PV have become the lowest-cost renewable alternatives and are expected to dominate the power supply matrix in many countries worldwide. However, wind and solar are inherently variable renewable energy sources (vRES) and their characteristics pose new challenges for power systems and for the transition to a renewable energy-based power supply. Using new options for the integration of high shares of vRES is therefore crucial. In order to assess these options, we model the expansion pathways of win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…One additional option is a capacity mix from wind and solar PV that is endogenously optimized by the VAREO model. The other additional option included in the VAREO scenarios are system-friendly layouts for wind and solar PV [7,21]. Both options have the potential to improve the supply by vRES in comparison to the exogenously determined mix from wind and solar PV and the standard vRES layouts to which the CLASSIC scenarios are restricted.…”
Section: Step 1: Scenario Framework and Variable Renewable Energy Optmentioning
confidence: 99%
See 2 more Smart Citations
“…One additional option is a capacity mix from wind and solar PV that is endogenously optimized by the VAREO model. The other additional option included in the VAREO scenarios are system-friendly layouts for wind and solar PV [7,21]. Both options have the potential to improve the supply by vRES in comparison to the exogenously determined mix from wind and solar PV and the standard vRES layouts to which the CLASSIC scenarios are restricted.…”
Section: Step 1: Scenario Framework and Variable Renewable Energy Optmentioning
confidence: 99%
“…The system-friendly layouts entail wind turbines with higher full load hours (FLH) designed for low to medium wind resources as well as solar PV installations facing towards east and west for a better temporal coverage of daily consumption patterns by the resulting vRES feed-in. For the modelling of feed-in time series for system-friendly layouts in the VAREO scenarios, it is also referred [6,21]. The general idea of the optimized capacity mix and the system-friendly layouts is to minimize the surplus power production from vRES over the course of the residual load time series, also described as excess energy.…”
Section: Step 1: Scenario Framework and Variable Renewable Energy Optmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve this goal, a significant expansion of renewable energies especially in the electricity sector must be achieved [4]. For the electricity sector, most scenarios assume that a focus will be on the expansion of technologies providing electricity from renewable energy sources (RES-E) such as solar and wind [5][6][7]. Several studies have shown that an improved spatial distribution of RES-E capacities within Europe is helpful to balance the fluctuations of wind flow and solar radiation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Todays most anticipated change in the energy system is the transition to renewable energy generation sources and its expected effect on the elec-tricity grid (Tafarte et al 2019). Due to this ongoing energy transition in Germany, roughly 30% of electricity is gained from renewable sources such as wind, sun and biomass (Öko-Institut e.V.…”
Section: Introductionmentioning
confidence: 99%